Epigenetic regulation of TDP-43: potential implications for amyotrophic lateral sclerosis - Mengistu, D. Y.; Terribili, M.; Pellacani, C.; Ciapponi, L.; Marzullo, M. (Frontiers in Molecular Medicine, 2025)
Amyotrophic lateral sclerosis (ALS) is a multifactorial neurodegenerative disease characterized by the progressive degeneration of motor neurons. One of the key pathogenic factors implicated in ALS is TDP-43 (TAR DNA-binding protein 43), an RNA-binding protein encoded by the TARDBP gene. Under normal physiological conditions, TDP-43 predominantly resides in the nucleus, where it plays a critical role in regulating gene expression, alternative splicing, RNA transport, and stability. In ALS, TDP-43 undergoes pathological mislocalization from the nucleus to the cytoplasm, disrupting its normal function and contributing to disease progression. The nuclear loss of TDP-43 leads to widespread dysregulation of RNA metabolism. Moreover, mislocalized TDP-43 aggregates in the cytoplasm, acquires toxic properties that sequester essential RNA molecules and proteins. Importantly, deviations in TDP-43 levels, whether excessive or reduced, can lead to cellular dysfunction, and contribute to disease progression, highlighting the delicate balance required for neuronal health. Emerging evidence suggests that epigenetic mechanisms may play a crucial role in regulating TARDBP expression and, consequently, TDP-43 cellular levels. Epigenetic modifications such as DNA methylation, histone modifications, and non-coding RNAs are increasingly recognized as modulators of gene expression and cellular function in neurodegenerative diseases, including ALS. Dysregulation of these processes could contribute to aberrant TARDBP expression, amplifying TDP-43-associated pathologies. This review explores and summarizes the recent findings on how specific epigenetic modifications influence TDP-43 expression and discusses their possible implications for disease progression.